2011
DOI: 10.2166/wst.2011.010
|View full text |Cite
|
Sign up to set email alerts
|

Full scale membrane bioreactor treatment of hospital wastewater as forerunner for hot-spot wastewater treatment solutions in high density urban areas

Abstract: Membrane Bioreactors (MBR) are a very attractive option for the treatment of hospital wastewater and elimination of pharmaceuticals in high density urban areas. The present investigation showed that, depending on the substance, between 19% and 94% of the level of antibiotics found in the environment originate from hospitals. Because of their ecotoxic potential, hospital wastewaters can have a significant impact on the environment. The segregation of these wastewaters and their separate treatment at the source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 7 publications
3
38
0
Order By: Relevance
“…(49). All in all, our findings are in line with other published hospital wastewater studies (35), and confirm differences in the loading patterns for specific pharmaceuticals, depending on several factors reported earlier (37,50). We believe that further investigation should look into these loading patterns.…”
Section: Pharmaceutical Concentrations In Hospital Wastewater and Thesupporting
confidence: 92%
“…(49). All in all, our findings are in line with other published hospital wastewater studies (35), and confirm differences in the loading patterns for specific pharmaceuticals, depending on several factors reported earlier (37,50). We believe that further investigation should look into these loading patterns.…”
Section: Pharmaceutical Concentrations In Hospital Wastewater and Thesupporting
confidence: 92%
“…Compared to households, antinflammatory drugs such as diclofenac (I EP = 0.0830) and ibuprofen (I EP = 0.0493), contribute 8% and 5%, respectively, to WW discharge. Other studies revealed similar results: between 1 and 10% for diclofenac and ibuprofen (Beier et al, 2011;Heberer and Feldmann, 2005;Langford and Thomas, 2009;Verlicchi et al, 2012b).…”
Section: Regional Comparison Of Consumed Pharmaceuticalssupporting
confidence: 62%
“…In fact, more pronounced contributions were described in literature for antibiotics (Beier et al, 2011;Ort et al, 2010;Thomas et al, 2007;Verlicchi et al, 2012a), reaching, in some cases, contributions as high as 272% (ciprofloxacin) (Thomas et al, 2007), 94% (clarithromycin) (Beier et al, 2011) or 67% (azithromycin) (Verlicchi et al, 2012a). On the other hand, for some of the most consumed analgesics/NSAIDs (for instance, ibuprofen, diclofenac or acetaminophen) hospital contribution reported in literature did not exceed 15% (Beier et al, 2011;Langford and Thomas, 2009;Thomas et al, 2007;Verlicchi et al, 2012a), which is in agreement with our results in what concern to ibuprofen and diclofenac (contribution up to 4.2 and 9.5%, respectively) (data not shown), however for acetaminophen, the contribution of university and general hospitals went to 483 and 115%, respectively (data not shown). Nevertheless, the X-ray contrast agent iopromide, which had a mean total mass load of approximately 303 g d − 1 coming from hospital effluents, only contributed with approximately 13% of its total mass load found in WWTP influent, though Ort et al (2010) reported a minor contribution (less than 5%).…”
Section: Occurrence Of Pharmaceuticals In Urban Wastewaters: Loads Imentioning
confidence: 99%
“…Nevertheless, few data is available on the contribution of hospital effluents towards the load of pharmaceuticals in WWTPs (Beier et al, 2011;Langford and Thomas, 2009;Ort et al, 2010;Thomas et al, 2007;Verlicchi et al, 2012a). At the same time, available data regarding the environmental risk posed by hospital effluents to aquatic organisms is still sparse and often limited to predicted (Escher et al, 2011;Souza et al, 2009) rather than measured concentrations (Verlicchi et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%